Pengaruh Metode Pembelajaran Project Citizen Terhadap Motivasi Belajar Siswa Kelas X di SMA Negeri 1 Gaung Kabupaten Indragiri Hilir - Dani, Rahmat; Supentri, Supentri; Haryono, Haryono (Journal of Education Technology Information Social Sciences and Health, 2025)
This research is motivated by the project citizen learning method, the learning motivation of class X students at SMA Negeri 1 Gaung Indragiri Hilir Regency. The formulation of the problem in ths research is how good is class X project citizen learning at SMA Negeri 1 Gaung Indragiri Hilir Regency, how good is the learning motivation of class X at SMA Negeri 1 Gaung Indragiri Hilir Regency. This research method is a pres experimental design type in the form of a one shot case study. the one shot case study. the one shot case study is a research design that only involves one experimental class which is carried out without a comparison class and without an initial test. Based on the research result, it is a follows: Based on the previously determined categories, it can be said that the learning motivation of students at SMA Negeri 1 Gaung Indragiri Hilir Regency after being treated with the project citizen method is classified as good, namely with a percentage of 71.4%. Based on the independent sample T-Tes tes calculation in table 4.28, tcount = 16.658 then determine df using the n-2 formula. The sample in this study was 67 so the price df = 67-2 = 65. With df 65 at the 5% significance level, the price t-table = 1.668. This shows that the hyphotesis in this study is accepted with tcount ttable (Ha is accepted and H0 is rejected). So it can be concluded that there is an influence of the Project Citizen (PC) Learning model on student learning motivation in civics subjects in class X SMA Negeri 1 Gaung Indragiri Hilir Regency.